Formbar kultur i förhandling för framtid: Gränsobjekt och gränsarbete i mångdisciplinär forskning - Pettersson, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2003)
This article deals with how co-workers in a multidisciplinary research arena can be analysed through the concept of boundary object and boundary work. A boundary object might be a scientific object or concept, in this article the concept of cultural sciences. The boundary object links persons with different disciplinary backgrounds together. This means that the boundary objects is exposed to negotiations and debating between different scientific arenas, disciplines and single individuals, including lay persons. In the scientific so called boundary work at Tools for Creativity, there is no explicit disciplinary culture, no expressed disciplinary identity. With the emergence of multidisciplinary research institutes, it is important to study how different members try to cooperate and negotiate knowledge claims, scientific skills and common goals. In the texts, there is firstly boundary works separating the external field from the internal arena of co-workers from different disciplines, taken from the discussion concerning the role of the cultural sciences in the activities and operations. In the boundary work, both those perspectives are negotiated. There are no doubts about the knowledge claims and the applications of information technology. The aims of the application can only be strengthened with the help from supplemented knowledge: the cultural sciences. Second, in an effort to integrate the latter, the knowledge perspectives of the cultural sciences are defined, criticized, called into question and eventually made agreeable to everyone. The concept of cultural science is extensively defined in the texts — "The Interactive Institute. Plans for a Swedish national laboratory for art, communication, and technology 1998 05 19" and the appendix — and is also a concept in the making. People inhibit different social worlds and scientific and multidisciplinary contexts, a heterogeneous group with different competences and research goals. Analysing a post-disciplinary research arena such as the Interactive Institute and Tools for Creativity is important for understanding practices within and perspectives on today's knowledge society. In analysing research norms, visions and demands in texts and daily work, one can achieve an understanding on how knowledge is being produced and negotiated as well as established.